If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(2x+-7)=-4x+14
We move all terms to the left:
-2(2x+-7)-(-4x+14)=0
We add all the numbers together, and all the variables
-2(2x-7)-(-4x+14)=0
We multiply parentheses
-4x-(-4x+14)+14=0
We get rid of parentheses
-4x+4x-14+14=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 6n2+8n=128 | | 12+2n=-(4-2) | | 5×50=200+x= | | 7(2-x)+x=2(x+7) | | 7+7x+41=16x-1 | | 7+7x=41 | | 2x+5/8=3x-3/2 | | -1=-0.1c | | 4/x+2=10/x | | 1.5÷k=3 | | .33×x=1 | | 8-4z=16+4z | | 19+2x=25*x | | (8/x)/(12/x)=2/3 | | 5/2b-11/4=29/4 | | X^2+x-1=13 | | x/6-3(x-4)/5=2-x-1/10 | | -4(7-10a)=152 | | -4(7-10a)=-152 | | 3.3=t/4.7 | | 50+x+59+80=180 | | x-(x*3.5/100)=20 | | x-3.5/100=20 | | 12=4(2x−5) | | 2x+1=-4x-25 | | -4(7-10a)=-68 | | 3(.5i-6)=12 | | 3(.5i-6=12 | | -9Y-8(-3y)=12 | | b/4-2=-7 | | 3x/3-12/3=x-4 | | 3x-12/3=x-4 |